2020
DOI: 10.1101/2020.02.26.963991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LSP1-myosin1e bi-molecular complex regulates focal adhesion dynamics and cell migration

Abstract: Telephone: +49 241 8085248Running head: LSP1-myosin1e complex regulates cell migration. Abstract Several cytoskeleton-associated proteins and signalling pathways work in concert to regulate actin cytoskeleton remodelling, cell adhesion and migration. We have recently demonstrated that the bi-molecular complex between the leukocyte-specific protein 1 (LSP1) and myosin1e controls actin cytoskeleton remodelling during phagocytosis. In this study, we show that LSP1 down regulation severely impairs cell migration, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…For this purpose, fluorescence recovery after photobleaching (FRAP) microscopy was used to determine the kinetics of zyxin at focal adhesions. Specifically, a fixed portion of focal adhesions in wild-type and Gas2L1 KO Sertoli cells expressing RFP-zyxin was bleached with a short, high-power laser impulse and the recovery of the fluorescence signal within this area recorded over time [ 51 , 61 , 72 , 73 ]. As shown in Fig 7 , in both wild-type and Gas2L1 KO Sertoli cells, the recovery of RFP-zyxin signal within the bleached area rapidly increased and reached a steady-state level after 200–250 seconds regardless of the substrate ( Fig 7A and 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, fluorescence recovery after photobleaching (FRAP) microscopy was used to determine the kinetics of zyxin at focal adhesions. Specifically, a fixed portion of focal adhesions in wild-type and Gas2L1 KO Sertoli cells expressing RFP-zyxin was bleached with a short, high-power laser impulse and the recovery of the fluorescence signal within this area recorded over time [ 51 , 61 , 72 , 73 ]. As shown in Fig 7 , in both wild-type and Gas2L1 KO Sertoli cells, the recovery of RFP-zyxin signal within the bleached area rapidly increased and reached a steady-state level after 200–250 seconds regardless of the substrate ( Fig 7A and 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…LSP1 regulates macrophage podosome properties: the levels of LSP1 control the frequency and amplitude of podosome oscillations, and interfering with LSP1 expression reduces podosome life span and the protruding forces they exert on the extracellular matrix (Cervero et al, 2018). Moreover, lack of LSP1 was recently shown to affect the microtubule network in macrophages (Schäringer et al, 2021). Here we found that in the absence of TUBB6, podosome have longer life-span and we found increased amounts of LSP1 in the S2 fraction of Tubb6 KO osteoclasts, suggesting that LSP1 may participate in the control of actin-dynamics in osteoclasts in a TUBB6-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…LSP1 regulates macrophage podosome properties: the levels of LSP1 control the frequency and amplitude of podosome oscillations, and interfering with LSP1 expression reduces podosome life span and the protruding forces they exert on the extracellular matrix (Cervero et al, 2018). Moreover, lack of LSP1 was recently shown to affect the microtubule network in macrophages (Schäringer et al, 2021). Here we found that in the absence of TUBB6, podosome have longer life-span and we found increased amounts of LSP1 in the S2 fraction of Tubb6 KO osteoclasts, suggesting that LSP1 may participate in the control of actin-dynamics in osteoclasts in a TUBB6-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%